Spirituality and Self-Efficacy in Caregivers of Patients with Neurodegenerative Disorders: An Overview of Spiritual Coping Styles - González-Rivera, Juan Aníbal (Religions, 2018)
The objective of this research was to assess the effect of spirituality and self-efficacy in the mental health of caregivers of patients with neurodegenerative disorders. Four styles of spiritual coping were examined to identify which of them can function as protective or risk factors for caregivers of patients with neurodegenerative disorders. Interviews were conducted face-to-face to 116 caregivers of patients diagnosed with some type of neurodegenerative disorder. The results showed that caregivers with a selfless spiritual coping style exhibit significantly higher depression, stress, and perceived overload than those with a collaborative style. No statistically significant differences were found between the means of the other styles of spiritual coping. Simultaneously, it was found that the selfless spiritual coping style is a risk factor for overload, depression, and stress. The study is a first step in understanding how spirituality interacts with self-efficacy to protect the mental health of caregivers of dementia patients in Puerto Rico. Our results theoretically and empirically support the functional compatibility of both psychological resources.